Point of care testing using rapid automated antigen testing for SARS-COV-2 in care homes – an exploratory safety, usability and diagnostic agreement evaluation. Issue 6 (December 2021) - Micocci, Massimo; Buckle, Peter; Hayward, Gail; Allen, A Joy; Davies, Kerrie; Kierkegaard, Patrick; Spilsbury, Karen; Thompson, Carl; Astle, Anita; Heath, Ros; Sharpe, Claire; Akrill, Cyd; et al.
Introduction: Successful adoption of POCTs (Point-of-Care tests) for COVID-19 in care homes requires the identification of ideal use cases and a full understanding of the contextual and usability factors that affect test results and minimise biosafety risks. This paper presents a scoping-usability and test performance study of a microfluidic immunofluorescence assay for COVID-19 in care homes. Methods: A mixed-methods evaluation was conducted in four UK care homes to scope usability and to assess the agreement with qRT-PCR. A dry run with luminescent dye was conducted to explore biosafety issues. Results: The agreement analysis was conducted on 227 asymptomatic participants (159 staff and 68 residents) and 14 symptomatic participants (5 staff and 9 residents). Asymptomatic specimens showed 50% (95% CI:1.3%−98.7%) positive agreement and 96% (95% CI: 92.5%−98.1%) negative agreement with overall prevalence and bias-adjusted Kappa (PABAK) of 0.911 (95% CI: 0.857−0.965). Symptomatic specimens showed 83.3% (95% CI: 35.9%−99.6%) positive agreement and 100% (95% CI: 63.1%−100%) negative agreement with overall prevalence and bias-adjusted Kappa (PABAK) of 0.857 (95% CI: 0.549−1). The dry run highlighted four main sources of contamination that led to the modification of the standard operating procedures. Simulation post-modification showed no further evidence of contamination. Conclusion: Careful consideration of biosafety issues and contextual factors associated with care home are mandatory for safe use the POCT. Whilst POCT may have some utility for ruling out COVID-19, further diagnostic accuracy evaluations are needed to promote effective adoption.